Lithium iron phosphate battery

JP7668889B2Active Publication Date: 2025-04-25SHENZHEN CAPCHEM TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2023552071
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-04-13
Filing Date
2022-03-29
Publication Date
2025-04-25
Estimated Expiration
2042-03-29

AI Technical Summary

Technical Problem

Lithium iron phosphate batteries face challenges with high energy density gaps compared to ternary batteries, and increasing compaction density leads to issues like Fe ion elution, oxidation of electrolyte, lithium dendrite formation, and safety risks, limiting their application and performance.

Method used

A lithium iron phosphate battery design incorporating a positive electrode with 2.3 to 2.8 g/cc density, using a non-aqueous electrolyte with vinylene carbonate and a compound represented by Structural Formula 1, forming an interfacial film to enhance lithium ion transfer, reduce redox reactions, and suppress Fe ion elution and lithium dendrite formation.

Benefits of technology

The interfacial film improves high-temperature cycling and safety performance by enhancing lithium ion conductivity and protecting electrode materials, effectively reducing Fe ion elution and dendrite formation, thus improving battery stability and safety.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 00000030_0000
    Figure 00000030_0000
  • Figure 00000030_0001
    Figure 00000030_0001
  • Figure 00000031_0000
    Figure 00000031_0000
Patent Text Reader

Abstract

In order to overcome the problems of lithium dendrites and iron ion elution present in existing highly compressed lithium iron phosphate batteries, the present invention provides a lithium iron phosphate battery. The lithium iron phosphate battery includes a positive electrode, a negative electrode, and a non-aqueous electrolyte. The positive electrode includes a positive electrode material layer, and the positive electrode material layer has a compressed density of 2.3 to 2.8 g / cc. The positive electrode material layer includes a positive electrode active material, and the positive electrode active material includes LiFePO4. The non-aqueous electrolyte includes a solvent, an electrolyte salt, vinylene carbonate, and a compound represented by structural formula 1: ADBEC Structural formula 1 The amount of the compound represented by the structural formula 1 added is 0.01 to 5%, with the total mass of the non-aqueous electrolyte being taken as 100%. The lithium iron phosphate battery provided by the present invention employs a combination of vinylene carbonate and the compound represented by the structural formula 1, thereby making it possible to suppress the generation of lithium dendrites at the negative electrode interface and the dissolution of Fe from the positive electrode, and ultimately to improve the high temperature performance, safety performance, and other performances of the high-packed density lithium iron phosphate battery.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to the technical field of secondary batteries, and in particular to lithium iron phosphate batteries. [Background technology]

[0002] Lithium-ion batteries have the advantages of high operating voltage, long cycle life, large energy density, no memory effect, etc., and have been widely used in mobile communications, notebook computers and other fields since their introduction into the market in 1991. In recent years, with the rapid development and popularization of new energy vehicles, consumers' requirements for the energy density of lithium-ion batteries are increasing. Compared with ternary batteries, lithium iron phosphate batteries have more advantages in terms of cycle life, safety, and cost, but there is still a large gap between the energy density of lithium iron phosphate and the energy density of ternary materials. At present, the energy density of single-component lithium iron phosphate batteries is mainly improved by increasing the compression density of the lithium iron phosphate positive electrode.

[0003] However, if the compaction density of lithium iron phosphate positive electrode material is blindly increased, firstly, the dissolution of Fe ions in the positive electrode will increase, and the oxidation and decomposition phenomenon of the electrolyte will become more intense, thereby reducing the performance of the battery in high-temperature storage and cycle. Secondly, this will lead to the formation of lithium dendrites at the electrode interface, which will cause short circuits and fires in the battery, seriously affecting the safety performance of the battery. This limits the application of high compaction density lithium iron phosphate positive electrode materials. Although manufacturers of positive electrode materials have also used various doping and coating to improve the stability of the positive electrode material structure, it is still a great challenge to use the current commercially available electrolyte in the high compaction lithium iron phosphate positive electrode material system to improve problems such as high-temperature cycle, high-temperature storage, and Fe ion dissolution at high temperature. Therefore, it is of relatively great significance to develop an additive for lithium iron phosphate batteries with high compaction density (2.3-2.8g / cc) and improve the electrolyte of high-temperature storage, high-temperature cycle, and Fe ion dissolution of lithium iron phosphate batteries. Summary of the Invention

[0004] The present invention provides a lithium iron phosphate battery that addresses the problems of lithium dendrites and iron ion elution in existing highly compressed lithium iron phosphate batteries.

[0005] The technical solutions adopted by the present invention to solve the above technical problems are as follows: The present invention provides a lithium iron phosphate battery. The lithium iron phosphate battery includes a positive electrode, a negative electrode, and a non-aqueous electrolyte. The positive electrode includes a positive electrode material layer, and the positive electrode material layer has a compressed density of 2.3 to 2.8 g / cc. The positive electrode material layer includes a positive electrode active material, and the positive electrode active material includes LiFePO4. The non-aqueous electrolyte solution includes a solvent, an electrolyte salt, vinylene carbonate, and a compound represented by structural formula 1: ADBEC Structural formula 1 In the formula, A, B, and C are each independently selected from a group containing a cyclic carbonate group, a cyclic sulfate group, a cyclic sulfite group, a cyclic sulfonate group, a cyclic sulfone group, a cyclic sulfoxide group, a cyclic carboxylate group, or a cyclic acid anhydride group; D and E are each independently selected from a single bond or a group containing an alkylene group, an ether bond, a sulfur-oxygen double bond, or a carbon-oxygen double bond; The amount of the compound represented by the structural formula 1 added is 0.01 to 5%, with the total mass of the nonaqueous electrolyte being 100%.

[0006] Optionally, the amount of vinylene carbonate added is 0.01 to 5%, and more preferably 0.1 to 2%, based on the total mass of the non-aqueous electrolyte solution being 100%.

[0007] Optionally, the positive electrode surface is probed by X-ray photoelectron spectroscopy to obtain a Carbon 1s peak at 284.5 eV and a characteristic S peak in the 162-174 eV region.

[0008] Optionally, the charge / discharge voltage range of the lithium iron phosphate battery is 2.0-3.8V.

[0009] Optionally, the number of cyclic carbonate groups, cyclic sulfate groups, cyclic sulfite groups, cyclic sulfonate groups, cyclic sulfone groups, cyclic sulfoxide groups, cyclic carboxylate groups, and cyclic acid anhydride groups contained by A, B, and C independently is 1 to 5, and the total number of cyclic carbonate groups, cyclic sulfate groups, cyclic sulfite groups, cyclic sulfonate groups, cyclic sulfone groups, cyclic sulfoxide groups, cyclic carboxylate groups, and cyclic acid anhydride groups contained by A, B, and C is 10 or less.

[0010] Optionally, A and C are each independently selected from the group represented by formula 2: JPEG2024508296000002.jpg35170JPEG2024508296000003.jpg61170

[0011] Optionally, B is selected from the group represented by structure 3: JPEG2024508296000004.jpg22170JPEG2024508296000005.jpg35170

[0012] Optionally, D and E are each independently selected from the group represented by formula 4: JPEG2024508296000006.jpg17170JPEG2024508296000007.jpg35170

[0013] Optionally, D and E are each independently selected from a single bond or a C1-C5 alkylene group, and A, B and C are each independently selected from a substituted or unsubstituted cyclic carbonate group, cyclic sulfate group, cyclic sulfite group, cyclic sulfonate group, cyclic sulfone group, cyclic sulfoxide group, cyclic carboxylate group or cyclic acid anhydride group. When A, B or C is substituted, the substituent is selected from a halogen, an alkyl group or a halogenated alkyl group.

[0014] Optionally, A and C are the same as each other, A and B are the same as or different from each other, and D and E are the same as each other.

[0015] Optionally, the compound represented by formula 1 is selected from one or more of the following compounds: JPEG2024508296000008.jpg113170JPEG2024508296000009.jpg106170JPEG2024508296 000010.jpg106170JPEG2024508296000011.jpg99170JPEG2024508296000012.jpg212170

[0016] According to the lithium iron phosphate battery provided by the present invention, vinylene carbonate and a compound represented by structural formula 1 are added to a non-aqueous electrolyte, and the vinylene carbonate and the compound represented by structural formula 1 are involved in the formation of an interfacial film on the surface of the positive and negative electrodes. It is presumed that the decomposition product of vinylene carbonate and the decomposition product of the compound represented by structural formula 1 are combined to form an interfacial film of organic-inorganic bonding. This interfacial film can effectively improve the lithium ion migration speed during the high-temperature cycle process of the battery, and at the same time has a relatively good protective effect on the electrode material, reducing the oxidation-reduction reaction between the electrolyte and the electrode material, inhibiting the generation of lithium dendrites at the negative electrode interface and the dissolution of Fe ions from the positive electrode, and ultimately improving the high-temperature performance, safety performance, and other performances of the lithium iron phosphate battery. [Brief description of the drawings]

[0017] [Figure 1] FIG. 10 is a full spectrum of the XPS spectrum of the battery positive electrode piece after capacity grading of the battery provided in Example 5 of the present invention. [Diagram 2] This is a detailed spectrum of the characteristic peaks in FIG. [Diagram 3] 1 is a SEM image of the negative electrode of the battery provided in Example 5 of the present invention after 1000 cycles. [Figure 4] 1 is a SEM image of the negative electrode of the battery provided in Comparative Example 1 of the present invention after 1000 cycles. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0018] In order to further clarify the technical problems, technical solutions and beneficial effects of the present invention, the present invention will be described in more detail below in combination with drawings and examples. It should be understood that the specific examples described herein are used for the interpretation of the present invention and are not intended to limit the present invention.

[0019] An embodiment of the present invention provides a lithium iron phosphate battery including a positive electrode, a negative electrode, and a non-aqueous electrolyte. The positive electrode includes a positive electrode material layer, and the positive electrode material layer has a compressed density of 2.3 to 2.8 g / cc. The positive electrode material layer includes a positive electrode active material, and the positive electrode active material includes LiFePO4. The non-aqueous electrolyte solution includes a solvent, an electrolyte salt, vinylene carbonate, and a compound represented by structural formula 1: ADBEC Structural formula 1 In the formula, A, B, and C are each independently selected from groups containing a cyclic ester group or a cyclic acid anhydride group, the cyclic ester group including one or more of a cyclic carbonate group, a cyclic sulfate group, a cyclic sulfite group, a cyclic sulfonate group, a cyclic sulfone group, a cyclic sulfoxide group, and a cyclic carboxylate group. D and E are each independently selected from a single bond or a group containing an alkylene group, an ether bond, a sulfur-oxygen double bond, or a carbon-oxygen double bond. The amount of the compound represented by the structural formula 1 added is 0.01 to 5%, with the total mass of the nonaqueous electrolyte being 100%.

[0020] The inventors have speculated through research that vinylene carbonate and the compound represented by structural formula 1 are involved in the formation of an interfacial film on the surfaces of the positive and negative electrodes, and that the decomposition products of vinylene carbonate and the decomposition products of the compound represented by structural formula 1 together constitute an organic-inorganic interfacial film. This interfacial film can effectively improve the lithium ion migration speed during the high-temperature cycle process of the battery, and at the same time has a relatively good protective effect on the electrode material, reducing the oxidation-reduction reaction between the electrolyte and the electrode material, inhibiting the generation of lithium dendrites at the negative electrode interface and the dissolution of Fe ions in the positive electrode, and ultimately improving the high-temperature performance, safety performance, and other performances of the lithium iron phosphate battery.

[0021] Vinylene carbonate can form an organic interface with a polymer structure on the surface of the electrode, but in a high-compression density lithium iron phosphate system, such an organic interface on the negative electrode does not promote the movement of lithium ions, and accumulates on the surface of the negative electrode to form lithium dendrites. The reaction between the lithium dendrites and the electrolyte causes problems such as further deterioration of battery performance and leaching of iron ions. The inventors have found through experiments that adding vinylene carbonate and a compound represented by structural formula 1 to a non-aqueous electrolyte at the same time can form a better synergistic effect with a high-compression density lithium iron phosphate battery, and after adding the compound represented by structural formula 1, the compound represented by structural formula 1 can form an interface film containing special components on the surface of the electrode, that is, it can improve the lithium ion conduction rate of the interface film, protect the structure of the positive and negative electrodes, and improve the stability of the battery material under high-temperature cycles.

[0022] In a preferred embodiment, the amount of the compound represented by the structural formula 1 added is 0.1 to 2%.

[0023] In some examples, the surface of the positive electrode was detected by X-ray photoelectron spectroscopy. As shown in Figures 1 and 2, a carbon 1s peak was obtained at 284.5 eV, and a characteristic peak of S appeared in the region of 162-174 eV. This indicates that vinylene carbonate and the compound represented by structural formula 1 together form an interface film on the surface of the positive electrode. This interface film has a relatively excellent organic-inorganic composition, which obviously improves the performance of the highly compressed lithium iron phosphate battery.

[0024] In some embodiments, the amount of vinylene carbonate added is 0.01 to 5%, relative to the total mass of the non-aqueous electrolyte solution being 100%.

[0025] In a preferred embodiment, the amount of vinylene carbonate added is 0.1 to 2% based on the total mass of the nonaqueous electrolyte being 100%.

[0026] In the lithium iron phosphate battery, vinylene carbonate and the compound represented by structural formula 1 have a relatively good synergistic relationship. If the amount of either vinylene carbonate or the compound represented by structural formula 1 added is too small, it is difficult to obtain a relatively good synergistic effect. If the amount of either vinylene carbonate or the compound represented by structural formula 1 added is too large, not only will the film become too thick, causing an increase in impedance, but also the viscosity of the electrolyte will increase significantly, affecting the performance of the battery.

[0027] In some embodiments, the charge / discharge voltage range of the lithium iron phosphate battery is 2.0 to 3.8V.

[0028] In some embodiments, the number of cyclic carbonate groups, cyclic sulfate groups, cyclic sulfite groups, cyclic sulfonate groups, cyclic sulfone groups, cyclic sulfoxide groups, cyclic carboxylate groups, and cyclic acid anhydride groups contained independently by A, B, and C is 1 to 5, and the total number of cyclic carbonate groups, cyclic sulfate groups, cyclic sulfite groups, cyclic sulfonate groups, cyclic sulfone groups, cyclic sulfoxide groups, cyclic carboxylate groups, and cyclic acid anhydride groups contained by A, B, and C is 10 or less.

[0029] In some embodiments, A and C are each independently selected from the group represented by formula 2: JPEG2024508296000013.jpg31170JPEG2024508296000014.jpg61170

[0030] JPEG2024508296000015.jpg33170

[0031] In some embodiments, B is selected from the group represented by structure 3: JPEG2024508296000016.jpg23170JPEG2024508296000017.jpg34170

[0032] In some embodiments, D and E are each independently selected from the group represented by formula 4: JPEG2024508296000019.jpg19170JPEG2024508296000020.jpg46170

[0033] In some embodiments, A and C are the same as each other, A and B are the same as each other or different, and D and E are the same as each other.

[0034] When A and C are the same as each other and D and E are the same as each other, the compound represented by the formula 1 has a symmetric structure. Compared with the asymmetric structure, the compound represented by the formula 1 having a symmetric structure is easy to synthesize and has a high product yield, which is advantageous for reducing costs.

[0035] In some embodiments, D and E are each independently selected from a single bond or a C1-C5 alkylene group, and A, B, and C are each independently selected from a substituted or unsubstituted cyclic carbonate group, cyclic sulfate group, cyclic sulfite group, cyclic sulfonate group, cyclic sulfone group, cyclic sulfoxide group, cyclic carboxylate group, or cyclic acid anhydride group. Preferably, when A, B, or C is substituted, the substituent is selected from a halogen, a hydrocarbon group, or a halogenated hydrocarbon group. More preferably, when A, B, or C is substituted, the substituent is selected from a halogen, an alkyl group, or a halogenated alkyl group.

[0036] As an example, the compound represented by formula 1 can be selected from one or more of the following compounds: JPEG2024508296000021.jpg72170JPEG2024508296000022.jpg101170JPEG2024508296000023.jpg89170

[0037] In some embodiments, D and E are each independently selected from the group represented by formula 4: JPEG2024508296000024.jpg16170JPEG2024508296000025.jpg16170JPEG2024508296000026.jpg15170A, B, and C are each independently selected from a substituted or unsubstituted cyclic carbonate group, cyclic sulfate group, cyclic sulfite group, cyclic sulfonate group, cyclic sulfone group, cyclic sulfoxide group, cyclic carboxylate group, or cyclic acid anhydride group. Preferably, when A, B, or C is substituted, the substituent is selected from a halogen, a hydrocarbon group, or a halogenated hydrocarbon group. More preferably, when A, B, or C is substituted, the substituent is selected from a halogen, an alkyl group, or a halogenated alkyl group. As an example, the compound represented by formula 1 can be selected from one or more of the following compounds: JPEG2024508296000027.jpg102170JPEG2024508296000028.jpg80170JPEG2024508296000029.jpg140170

[0038] As an example, the compound represented by formula 1 can be selected from one or more of the following compounds: JPEG2024508296000030.jpg72170JPEG2024508296000031.jpg126170

[0039] The above are some of the compounds described in the claims of the present invention, but the present invention is not limited to these compounds and should not be construed as limiting the present invention.

[0040] Those skilled in the art, when they know the formula of the compound of formula 1, can know how to prepare said compound according to general knowledge in the field of chemical synthesis. For example:

[0041] Compound 1 can be prepared by the following method. Sorbitol, dimethyl carbonate, potassium hydroxide as an alkaline catalyst for methanol, and an organic solvent such as DMF are placed in a reaction vessel and reacted under heating conditions for several hours, after which a certain amount of oxalic acid is added to adjust the pH to neutral, and the mixture is filtered and recrystallized to obtain intermediate product 1. Next, intermediate product 1, carbonate ester, thionyl chloride, etc. are esterified under high temperature conditions to obtain intermediate product 2. Then, intermediate product 2 is oxidized using an oxidizing agent such as sodium periodate to obtain compound 1.

[0042] Compound 2 can be prepared by the following method. Diacetone-D-mannitol, dimethyl carbonate, methanol, potassium carbonate, dioxane, etc. are reacted under heating and stirring conditions for several hours, and then a certain amount of oxalic acid is added to adjust the pH to neutral, and the mixture is filtered and concentrated to obtain intermediate product 3. Intermediate product 3 is hydrolyzed by adding an appropriate amount of pure water, carbonate ester, acid, etc. to obtain intermediate product 4. Then, intermediate product 4, thionyl chloride, and carbonate ester solvent are prepared under heating conditions to obtain intermediate product 5. Finally, intermediate product 5 is oxidized using an oxidizing agent such as sodium periodate to obtain compound 2.

[0043] In some embodiments, the solvent comprises one or more of an ether solvent, a nitrile solvent, a carbonate solvent, and a carboxylate solvent.

[0044] The ether solvent includes a cyclic ether or a chain ether.

[0045] Examples of cyclic ethers may include, for example, one or more of 1,3-dioxolane (DOL), 1,4-dioxane (DX), crown ethers, tetrahydrofuran (THF), 2-methyltetrahydrofuran (2-CH3-THF), and 2-trifluoromethyltetrahydrofuran (2-CF3-THF).

[0046] Examples of linear ethers include, for example, one or more of dimethoxymethane (DMM), 1,2 dimethoxyethane (DME), and diethylene glycol dimethyl ether (TEGDME).

[0047] Examples of nitrile solvents may include, for example, one or more of acetonitrile, glutaronitrile, and malononitrile.

[0048] The carbonate ester solvent includes a cyclic carbonate ester or a chain carbonate ester.

[0049] Examples of cyclic carbonates include one or more of ethylene carbonate (EC), propylene carbonate (PC), γ-butyrolactone (GBL), and butylene carbonate (BC).

[0050] Examples of the chain carbonate ester include one or more of dimethyl carbonate (DMC), methyl ethyl carbonate (EMC), diethyl carbonate (DEC), methyl n-propyl carbonate, ethyl n-propyl carbonate, and dipropyl carbonate (DPC).

[0051] The carboxylate solvent includes a cyclic carboxylate or a chain carbonate.

[0052] Examples of cyclic carboxylic acid esters may include, for example, one or more of γ-butyrolactone, γ-valerolactone, and δ-valerolactone.

[0053] Examples of the chain carbonate ester include one or more of methyl acetate (MA), ethyl acetate (EA), propyl acetate (EP), butyl acetate, propyl propionate (PP), and butyl propionate.

[0054] In some embodiments, the electrolyte salt is selected from lithium salts. In preferred embodiments, the electrolyte salt is selected from LiPF6, LiBF4, LiBOB, LiDFOB, LiN(SO2CF3)2, LiN(SO2C2F5)2, LiC(SO2CF3)3, LiN(SO2F)2, LiClO4, LiAsF6, LiSbF6, LiCF3SO3, Li2B 10 Cl 10 , a lithium salt of a lower aliphatic carboxylate, LiAlCl4, LiDFOP, LiPO2F2. In a more preferred embodiment, the electrolyte salt is selected from one or more of LiPF6, LiPO2F2, and LiFSI.

[0055] In some embodiments, the concentration of the electrolyte salt in the non-aqueous electrolyte solution is 0.1 mol / L to 8 mol / L. In a preferred embodiment, the concentration of the electrolyte salt in the non-aqueous electrolyte solution is 0.5 mol / L to 4 mol / L. Specifically, the concentration of the electrolyte salt may be 0.5 mol / L, 1 mol / L, 1.5 mol / L, 2 mol / L, 2.5 mol / L, 3 mol / L, 3.5 mol / L, or 4 mol / L.

[0056] In some embodiments, the non-aqueous electrolyte further comprises an auxiliary additive, which comprises at least one of a fluorinated cyclic carbonate compound, a sultone compound, an aromatic additive, a fluorinated anisole compound, a dicarboxylic acid anhydride, lithium difluorophosphate, ethylene sulfate (DTD), lithium bis(fluorosulfonyl)imide (LiFSI), methylenemethane disulfonate, tris(trimethylsilyl)phosphate, and tris(trimethylsilyl)borate.

[0057] In some embodiments, the fluorinated cyclic carbonate based compound comprises one or more of fluorinated ethylene carbonate (FEC), 4,4-difluoroethylene carbonate, 4,5-difluoroethylene carbonate, 4-fluoro-4-methylethylene carbonate, 4,5-difluoro-4-methylethylene carbonate, 4-fluoro-5-methylethylene carbonate, 4,4-difluoro-5-methylethylene carbonate, 4-(fluoromethyl)ethylene carbonate, 4-(difluoromethyl)ethylene carbonate, 4-(trifluoromethyl)ethylene carbonate, 4-(fluoromethyl)-4-fluoroethylene carbonate, 4-(fluoromethyl)-5-fluoroethylene carbonate, 4-fluoro-4,5-dimethylethylene carbonate, 4,5-difluoro-4,5-dimethylethylene carbonate, 4,4-difluoro-5,5-dimethylethylene carbonate.

[0058] When the non-aqueous electrolyte contains a fluorinated cyclic carbonate compound, the content of the fluorinated cyclic carbonate compound is 0.1 to 30% relative to the total mass of the non-aqueous electrolyte, which is taken as 100%.

[0059] In some embodiments, the sultone-based compound is selected from one or more of 1,3-propane sultone (PS), 1,4-butane sultone (BS), and 1,3-propene sultone (PST).

[0060] When the non-aqueous electrolyte contains a sultone compound, the content (mass percentage) of the sultone compound is 0.1 to 5% relative to the total mass of the non-aqueous electrolyte, which is taken as 100%.

[0061] In some embodiments, the aromatic additive includes one or more of aromatic compounds such as biphenyl, alkylbiphenyl, terphenyl, partially hydrogenated terphenyl, cyclohexylbenzene, tert-butylbenzene, tert-amylbenzene, diphenyl ether, dibenzofuran, and 2-fluorobiphenyl, o-cyclohexylfluorobenzene, and p-cyclohexylfluorobenzene.

[0062] When the non-aqueous electrolyte contains an aromatic additive, the content (mass percentage) of the aromatic additive is 0.1 to 5% relative to the total mass of the non-aqueous electrolyte, which is taken as 100%.

[0063] In some embodiments, the fluorine-containing anisole compound comprises one or more of 2,4-difluoroanisole, 2,5-difluoroanisole, and 2,6-difluoroanisole.

[0064] When the non-aqueous electrolyte contains a fluorine-containing anisole compound, the content (mass percentage) of the fluorine-containing anisole compound is 0.1 to 5% relative to the total mass of the non-aqueous electrolyte, which is taken as 100%.

[0065] In some embodiments, the dicarboxylic acid anhydride comprises one or more of succinic acid, maleic acid, and phthalic acid.

[0066] When the non-aqueous electrolyte solution contains a dicarboxylic acid anhydride, the content (mass percentage) of the dicarboxylic acid anhydride is 0.1 to 5% relative to the total mass of the non-aqueous electrolyte solution, which is taken as 100%.

[0067] In some embodiments, when the non-aqueous electrolyte contains lithium difluorophosphate, the content (mass percentage) of the lithium difluorophosphate is 0.1 to 2%, relative to the total mass of the non-aqueous electrolyte being 100%.

[0068] In some embodiments, when the non-aqueous electrolyte contains ethylene sulfate (DTD), the content (mass percentage) of the ethylene sulfate (DTD) is 0.1 to 5% with the total mass of the non-aqueous electrolyte being 100%.

[0069] In some embodiments, when the non-aqueous electrolyte contains lithium bis(fluorosulfonyl)imide (LiFSI), the content (mass percentage) of the lithium bis(fluorosulfonyl)imide (LiFSI) is 0.1 to 5%, with the total mass of the non-aqueous electrolyte being 100%.

[0070] In some embodiments, the auxiliary additives also include nitrogen-containing compounds such as 1-methyl-2-pyrrolidone, 1-methyl-2-piperidone, 3-methyl-2-oxazolidinone, 1,3-dimethyl-2-imidazolidone, N-methylsuccinimide, etc., hydrocarbon compounds such as heptane, octane, cycloheptane, etc., fluorine-containing aromatic compounds such as fluorobenzene, difluorobenzene, trifluorotoluene, etc., and the like.

[0071] Unless otherwise specified, the content (mass percentage) of any optional substance in the auxiliary additive in the nonaqueous electrolyte is generally in the range of 10% or less, and preferably the content (mass percentage) is 0.1 to 5%.

[0072] In a preferred embodiment, the co-additive is selected from one or more of 1,3-propane sultone, methylene methane disulfonate, fluorinated ethylene carbonate, and ethylene sulfate.

[0073] In some embodiments, the positive electrode further comprises a positive electrode current collector. The positive electrode material layer covers a surface of the positive electrode current collector. The positive electrode current collector is selected from a metal material capable of conducting electrons. Preferably, the positive electrode current collector comprises one or more of Al, Ni, and stainless steel. In a more preferred embodiment, the positive electrode current collector is selected from aluminum foil.

[0074] In some embodiments, the positive electrode layer further comprises a positive electrode binder and a positive electrode conductive agent. The positive electrode active material, the positive electrode binder and the positive electrode conductive agent are mixed to obtain the positive electrode layer.

[0075] The positive electrode binder includes one or more of thermoplastic resins such as polyvinylidene fluoride, vinylidene fluoride copolymers, polytetrafluoroethylene, vinylidene fluoride-hexafluoropropylene copolymers, tetrafluoroethylene-hexafluoropropylene copolymers, tetrafluoroethylene-perfluoroalkyl vinyl ether copolymers, ethylene-tetrafluoroethylene copolymers, vinylidene fluoride-tetrafluoroethylene copolymers, vinylidene fluoride-trifluoroethylene copolymers, vinylidene fluoride-trichloroethylene copolymers, vinylidene fluoride-fluorinated ethylene copolymers, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene copolymers, thermoplastic polyimide, polyethylene, and polypropylene, acrylic resins, and styrene-butadiene rubber.

[0076] The positive electrode conductive agent includes one or more of conductive carbon black, conductive carbon spheres, conductive graphite, conductive carbon fibers, carbon nanotubes, graphene, or reduced graphene oxide.

[0077] In some embodiments, the anode comprises an anode material layer, the anode material layer comprising an anode active material. The anode active material comprises one or more of a silicon-based anode, a carbon-based anode, a tin-based anode, and a lithium anode. The silicon-based anode comprises one or more of a silicon material, an oxide of silicon, a silicon-carbon composite, and a silicon alloy material. The carbon-based anode comprises one or more of graphite, hard carbon, soft carbon, graphene, and mesocarbon microbeads. The tin-based anode comprises one or more of tin, tin-carbon, tin-oxygen, and tin-metal compounds. The lithium anode comprises one or more of metallic lithium or a lithium alloy. The lithium alloy may be at least one of a lithium-silicon alloy, a lithium-sodium alloy, a lithium-potassium alloy, a lithium-aluminum alloy, a lithium-tin alloy, and a lithium-indium alloy.

[0078] In preferred embodiments, the anode active material is selected from one or more of artificial graphite, natural graphite, and silicon-oxygen-carbon. In some embodiments, the anode further comprises an anode current collector. The anode material layer covers a surface of the anode current collector. The anode current collector is selected from a metallic material capable of conducting electrons. Preferably, the anode current collector comprises one or more of Cu, Ni, and stainless steel. In more preferred embodiments, the anode current collector is selected from copper foil.

[0079] In some embodiments, the negative electrode layer further comprises a negative electrode binder and a negative electrode conductive agent. The negative electrode active material, the negative electrode binder and the negative electrode conductive agent are mixed to obtain the negative electrode layer.

[0080] The negative electrode binder includes one or more of thermoplastic resins such as polyvinylidene fluoride, vinylidene fluoride copolymers, polytetrafluoroethylene, vinylidene fluoride-hexafluoropropylene copolymers, tetrafluoroethylene-hexafluoropropylene copolymers, tetrafluoroethylene-perfluoroalkyl vinyl ether copolymers, ethylene-tetrafluoroethylene copolymers, vinylidene fluoride-tetrafluoroethylene copolymers, vinylidene fluoride-trifluoroethylene copolymers, vinylidene fluoride-trichloroethylene copolymers, vinylidene fluoride-fluorinated ethylene copolymers, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene copolymers, thermoplastic polyimide, polyethylene, and polypropylene, acrylic resins, and styrene butadiene rubber.

[0081] The negative electrode conductive agent includes one or more of conductive carbon black, conductive carbon spheres, conductive graphite, conductive carbon fibers, carbon nanotubes, graphene, or reduced graphene oxide.

[0082] In some embodiments, the battery further includes a diaphragm, which is located between the positive electrode and the negative electrode. The diaphragm may be an existing conventional diaphragm, such as a ceramic diaphragm, a polymer diaphragm, a nonwoven fabric, an inorganic-organic composite diaphragm, etc., including, but not limited to, monolayer PP (polypropylene), monolayer PE (polyethylene), bilayer PP / PE, bilayer PP / PP, and trilayer PP / PE / PP diaphragms.

[0083] The present invention will now be further described with reference to examples. 1. Examples 1 to 29 and Comparative Examples 1 to 13

[0084] 1) Preparation of electrolyte: Ethylene carbonate (EC) and methyl ethyl carbonate (EMC) were mixed according to a mass ratio of EC:EMC=3:7, then lithium hexafluorophosphate (LiPF6) was added until the molar concentration reached 1 mol / L, and then the additives in each table below were added. The amount of additive used was calculated based on the percentage of the total mass of the electrolyte.

[0085] 2) Manufacturing of positive electrodes The positive electrode active material lithium iron phosphate, conductive carbon black Super-P, and binder polyvinylidene fluoride (PVDF) were mixed in a mass ratio of 93:4:3, and then dispersed in N-methyl-2-pyrrolidone (NMP) to obtain a positive electrode slurry. The slurry was uniformly applied to both sides of an aluminum foil, baked and dried, rolled, and vacuum dried, and an aluminum lead wire was welded to the aluminum foil using an ultrasonic welder to obtain a positive electrode plate. The thickness of the plate was 120 to 150 μm. The compressed density of the positive electrode material layer is shown in the following tables.

[0086] 3) Manufacturing of negative electrodes The negative electrode active material modified natural graphite, conductive carbon black Super-P, binder styrene butadiene rubber (SBR), and carboxymethyl cellulose (CMC) were mixed in a mass ratio of 94:1:2.5:2.5, and then dispersed in deionized water to obtain a negative electrode slurry. The slurry was applied onto both sides of a copper foil, baked dry, pressed with a roller, and nickel lead wires were welded with an ultrasonic welder to obtain a negative electrode plate. The porosity of each test group and the control group after pressing with a roller is shown in Table 1.

[0087] 4) Battery cell manufacturing A 20 μm-thick polyethylene microporous membrane was placed between the positive and negative electrode plates as a diaphragm. The sandwich structure consisting of the positive and negative electrode plates and the diaphragm was then wound, after which the wound body was flattened and placed in an aluminum plastic film. The positive and negative electrode lead wires were then pulled out, and the aluminum plastic film was then sealed by thermocompression to obtain a battery cell into which electrolyte could be injected.

[0088] 5) Battery cell injection and formation In a glove box where the dew point was controlled to -40°C or less, the electrolyte prepared above was injected into the battery cell through the electrolyte injection hole. The amount of electrolyte must be such that the gaps in the battery cell are filled reliably. Next, the battery was charged at a constant current of 0.05C for 180 minutes, then at a constant current of 0.1C for 180 minutes, left for 24 hours, then shaped and sealed, and then further charged to 3.65V at a constant current of 0.2C, left at room temperature for 24 hours, and then discharged to 2.0V at a constant current of 0.2C. 2. Performance test

[0089] The lithium ion batteries produced in Examples 1 to 29 and Comparative Examples 1 to 13 were subjected to the following performance tests.

[0090] High temperature cycle performance test 1) At 45°C, the battery was charged to 3.65 V at a constant current of 1 C, then charged at a constant voltage until the current dropped to 0.1 C, and then discharged to 2.0 V at a constant current of 1 C. In this manner, the battery was cycled 1000 times, and the discharge capacity at the first week and the discharge capacity at the 1000th week were recorded, and the capacity retention rate was calculated by the following formula. Capacity retention rate = (1000th discharge capacity ÷ 1st week discharge capacity) × 100%

[0091] 2) 3.65V fully charged state, 60℃ storage test: At room temperature, the battery after capacity grading was charged at 0.5C to 3.65V, with a cut-off current of 0.02C, left for 5 minutes, and then discharged at 0.5C to 2.0V, recording the initial capacity D1. Next, the battery was charged at a constant current of 0.5C, with a constant voltage of 0.02C, with a cut-off current of 3.65V, to test the thickness T1, voltage, and internal resistance. The fully charged battery was stored in a thermostatic box at 60°C for 30 days, and the hot thickness of the battery was recorded as T2. After leaving the battery at room temperature for 4 hours, the cold thickness T3, voltage, and internal resistance of the battery were tested. Next, the battery was discharged at 0.5C to 2.0V, recording the sustained capacity D2, and after leaving it for 5 minutes, it was charged at a constant current of 0.5C, with a constant voltage of 0.02C, with a cut-off current of 3.65V, left for 5 minutes, and then discharged at 0.5C to 2.0V, recording the recovered capacity D3. Battery capacity maintenance rate (%)=D2 / D1*100%, Battery capacity recovery rate (%) = D3 / D1*100%

[0092] 3) Iron ion elution test: The battery was disassembled after the cycle, and the negative electrode and the negative electrode side diaphragm were removed and dissolved in a mixed solution of water: concentrated nitric acid = 2: 1 (mass ratio). After the digestion was completed, 20 g of the digestion liquid was taken and dispensed into a 50 ml reagent bottle, and the amount of iron ions dissolved on the negative electrode and the diaphragm was measured by an inductively coupled plasma optical emission spectrometer (ICP-OES).

[0093] 1. The test results obtained in Examples 1 to 12 and Comparative Examples 1 and 2 are shown in Table 1. JPEG2024508296000032.jpg148170

[0094] As can be seen from the test data of Examples 1 to 12 and Comparative Examples 1 and 2, the high compression density (2.5 g / cm 3 In a lithium iron phosphate battery, when vinylene carbonate (VC) and the compound represented by structural formula 1 are added simultaneously to the electrolyte, the high temperature cycle performance at 45° C. and the high temperature storage performance at 60° C. are significantly improved, and the elution of iron ions is effectively suppressed, compared with the case where vinylene carbonate (VC) and the compound represented by structural formula 1 are added alone. That is, the combination of additives provided by the present invention can significantly improve the high temperature cycle and storage performance of a high-packed density lithium iron phosphate battery.

[0095] From the test data of Examples 1 to 8, it can be seen that in the non-aqueous electrolyte of 2% VC, as the content of the compound represented by structural formula 1 increases, the performance after 1000 cycles at 45°C, 1C / 1C, and storage at 60°C for 30 days is initially good, but then deteriorates. When the amount of the compound represented by structural formula 1 added to the non-aqueous electrolyte is 0.5%, a good synergistic effect with 2% VC can be obtained, and the overall performance of the battery can be effectively improved. When the content exceeds 0.5%, the residual amount in the positive electrode piece also increases, and when the compound represented by structural formula 1 is excessive, side reactions inside the battery increase, the battery impedance increases, and it is disadvantageous to further improve the battery performance. When the content is less than 0.5%, the interface film formed on the negative electrode is not stable enough, and the improvement of the performance of the lithium iron phosphate battery is not obvious.

[0096] As can be seen from the test data of Examples 5, 9 to 12, based on the compound represented by structural formula 1 with an additive amount of 0.5% determined as above, as the additive amount of vinylene carbonate (VC) increases, the high temperature cycle performance of the lithium ion battery is initially good, but then decreases. In particular, when the additive amount of vinylene carbonate (VC) is 2%, it has an optimal synergistic effect with the compound represented by structural formula 1. If the additive amount of vinylene carbonate (VC) is too small, the film formation is not stable, and the improvement of the high temperature cycle performance of the lithium iron phosphate battery is not obvious. If the content of vinylene carbonate (VC) is too high, even if the compound represented by structural formula 1 is added, the increase in the thickness of the interface film due to the increase in the VC content cannot be suppressed, and the performance of the lithium iron phosphate battery is rather reduced.

[0097] 2. The test results obtained in Examples 5, 13 to 16 and Comparative Examples 1, 3 to 11 are shown in Table 2. JPEG2024508296000033.jpg158170

[0098] As can be seen from the test results of Examples 5, 13 to 16 and Comparative Examples 1, 3 to 11, by adding the compound represented by Structural Formula 1 to an electrolyte solution containing vinylene carbonate (VC), a high compressed density (2.3 to 2.8 g / cm 3 ) The high-temperature storage and cycle performance of the lithium iron phosphate battery has been effectively improved, and the low compression density (1.8~2.3g / cm 3 ) The high-temperature storage and cycle performance of the lithium iron phosphate battery is improved to some extent, but the effect of improvement is not clear. That is, the high compression density lithium iron phosphate battery (2.3~2.8g / cm 3 The effect of the compound represented by formula 1 on the high-temperature cycle and storage performance of the lithium iron phosphate battery is more significant. The test results show that the compound represented by formula 1, together with VC, can form an interfacial film on the electrode surface, improve the lithium ion transfer rate of the high-pressure lithium iron phosphate battery in processes such as high-temperature cycle, reduce the oxidation-reduction reaction between the electrolyte solvent and the electrode material, inhibit the formation of lithium dendrites at the negative electrode interface, and ultimately improve the high-temperature cycle and high-temperature storage performance of the lithium iron phosphate battery.

[0099] 3. The test results obtained in Examples 5, 17 to 27 and Comparative Examples 1 and 2 are shown in Table 3. JPEG2024508296000034.jpg166170

[0100] Comparing the test data of Examples 5, 17 to 26 and Comparative Examples 1 and 2, the high compression density (2.5 g / cm 3 In a lithium iron phosphate battery, the addition of various compounds represented by structural formula 1 to an electrolyte containing vinylene carbonate (VC) improves the high-temperature cycle performance at 45°C and the high-temperature storage performance at 60°C to various degrees, and effectively suppresses the elution of iron ions. This is because the compounds represented by structural formula 1 have a high compressed density (2.5 g / cm 3 This shows that the two materials have a commonality in that they work well together with vinylene carbonate (VC) in lithium iron phosphate batteries.

[0101] 4. The test results obtained in Examples 5, 28-29 and Comparative Examples 1, 12-13 are shown in Table 4. JPEG2024508296000035.jpg105170

[0102] As can be seen from the test data of Examples 5, 28 to 29 and Comparative Examples 1, 12 to 13, by further adding ethylene diamine sulfate (DTD) or methylene methane disulfonate (MMDS) to the non-aqueous electrolyte system of vinylene carbonate (VC) and the compound represented by structural formula 1, the high-temperature cycle performance and high-temperature storage performance of the highly compressed lithium iron phosphate battery can be further improved.

[0103] At the same time, comparing the test data of Example 5 and Comparative Examples 12 to 13, the compound represented by structural formula 1 in the vinylene carbonate (VC) non-aqueous electrolyte has a more significant improving effect on the high-density lithium iron phosphate battery than the case where ethylene sulfate (DTD) or methylene methane disulfonate (MMDS) is added to the vinylene carbonate (VC) non-aqueous electrolyte.

[0104] 5. After the lithium ion batteries obtained in Example 5 and Comparative Example 1 were cycled 1000 times, they were disassembled to obtain negative electrode pieces and photographed by SEM. The test structure obtained in Example 5 is shown in Figure 3, and the test results obtained in Comparative Example 1 are shown in Figure 4.

[0105] As can be seen from FIGS. 3 and 4, when only 2.0% VC was added to the electrolyte, obvious lithium dendrites (rod-like structures in FIG. 4) were present on the negative electrode piece after 1000 cycles in Comparative Example 1. In contrast, when 0.5% of the compound represented by Structural Formula 1 was added in addition to 2.0% VC in Example 1, almost no lithium dendrites were present on the negative electrode after 1000 cycles. Therefore, by adding a combination of the compound represented by Structural Formula 1 and vinylene carbonate (VC), the formation of lithium dendrites can be significantly suppressed.

[0106] The above description is only a preferred embodiment of the present invention, and the present invention is not limited thereto. As long as it falls within the spirit and principle of the present invention, all modifications, equivalent replacements, improvements, etc., made should be included within the protection scope of the present invention.

Claims

1. A lithium iron phosphate battery includes a positive electrode, a negative electrode, and a non-aqueous electrolyte, the positive electrode includes a positive electrode material layer, the positive electrode material layer has a compressed density of 2.3 to 2.8 g / cc, the positive electrode material layer includes a positive electrode active material, and the positive electrode active material is LiFePO 4 Including, The non-aqueous electrolyte solution includes a solvent, an electrolyte salt, vinylene carbonate, and a compound represented by structural formula 1: A-D-B-E-C Structural formula 1 In the formula, A, B, and C are each independently selected from a group containing a cyclic carbonate group, a cyclic sulfate group, a cyclic sulfite group, a cyclic sulfonate group, a cyclic sulfone group, a cyclic sulfoxide group, a cyclic carboxylate group, or a cyclic acid anhydride group; D and E are each independently selected from a single bond or a group containing an alkylene group, an ether bond, a sulfur-oxygen double bond, or a carbon-oxygen double bond; The amount of the compound represented by the structural formula 1 added is 0.01 to 5% based on the total mass of the non-aqueous electrolyte being 100%.

2. 2. The lithium iron phosphate battery according to claim 1, wherein the amount of vinylene carbonate added is 0.01 to 5%, and more preferably 0.1 to 2%, of the total mass of the nonaqueous electrolyte solution being 100%.

3. The lithium iron phosphate battery according to claim 1, characterized in that the positive electrode surface is detected by X-ray photoelectron spectroscopy, and a carbon 1s peak is obtained at 284.5 eV, and a characteristic peak of S appears in the region of 162 to 174 eV.

4. 2. The lithium iron phosphate battery according to claim 1, wherein the charge / discharge voltage range of the lithium iron phosphate battery is 2.0 to 3.8 V.

5. 2. The lithium iron phosphate battery according to claim 1, wherein the number of cyclic carbonate groups, cyclic sulfate groups, cyclic sulfite groups, cyclic sulfonate groups, cyclic sulfone groups, cyclic sulfoxide groups, cyclic carboxylate groups, and cyclic acid anhydride groups contained in A, B, and C is 1 to 5, and the total number of cyclic carbonate groups, cyclic sulfate groups, cyclic sulfite groups, cyclic sulfonate groups, cyclic sulfone groups, cyclic sulfoxide groups, cyclic carboxylate groups, and cyclic acid anhydride groups contained in A, B, and C is 10 or less.

6. A and C are each independently selected from the group represented by formula 2:

7. B is selected from the group represented by formula 3:

8. D and E are each independently selected from the group represented by formula 4:

9. 9. The lithium iron phosphate battery according to claim 1, wherein A and C are the same as each other, A and B are the same as or different from each other, and D and E are the same as each other.

10. 2. The lithium iron phosphate battery of claim 1, wherein the compound represented by the structural formula 1 is selected from one or more of the following compounds: